EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI CIHERANG DI KELURAHAN SEMPIDI KECAMATAN MENGWI KABUPATEN BADUNG - Anum, Hendrika; Kardi, Cening; Sukanteri, Ni Putu (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
The research objective is to determine the factors of production that affect the production of Ciherang rice in Sempidi Village. To find out the efficient use of production factors in the Ciherang rice farming in Sempidi Village. The research was carried out in Subak Petang, Sempidi Village, Mengwi District, Badung Regency. And carried out in November 2019. Determination of the location of research carried out deliberately. The results of this study indicate that production factors are affected by the production of Ciherang Rice Farming in Sempidi Village, namely: Planting area has a significant effect on production elasticity of 0.180, Ciherang Rice Seed has a significant effect on production elasticity of 0.167, Ponska Fertilizer has no significant effect with production elasticity of - 0.067, Liquid pesticides have no significant effect on production elasticity of -0.014, and Labor has a significant effect on production elasticity of 0.206. The level of efficiency of the use of production factors in Ciherang Rice Farming in Sempidi Village, namely: Efficient planting land area, Ciherang Rice Seed has not efficient, Ponska Fertilizers, Liquid pesticides, and Labor is not efficient.